Perceive social support, academic self-efficacy, and learning engagement among high school students in China - Yang, Liu; Hooi Lian, Lim (International Journal of Evaluation and Research in Education (IJERE), 2025)
The aim of this study was to analyze the mediating role of academic self-efficacy in the relationship between perceive social support and learning engagement among Chinese senior high school students. A quantitative research method was adopted, and 572 Chinese senior high school students from Inner Mongolia Autonomous Region in China completed three self-report questionnaires. Correlation analysis revealed that senior high school students perceive social support, academic self-efficacy, and learning engagement were significantly correlated with each other. In addition, structural equation modeling analysis showed that perceive social support exerted its indirect effect on learning engagement through the mediation of academic self-efficacy. These findings have practical implication for government policymakers, education administrators, teachers, students, and parents, informing evidence-based policies, interventions, and strategies to enhance learning engagement and academic success.